Prevalence and correlates of complementary and alternative medicine utilization among infertile women attending selected fertility clinics in Khartoum state - Masani Elmahdy; Faiza Ali Nasor (PAGEPress Publications, 2024)
Infertility poses multifaceted challenges, prompting many women to explore complementary and alternative medicine (CAM). This study investigated CAM prevalence and types among infertile women in Khartoum. A descriptive cross-sectional study was conducted, involving 253 women. Data was collected through structured interviews, and descriptive and inferential statistics, with a significance level set at p>0.05. The mean age of the participants was 31.59±6.9 years, with 53.8% being graduates, 54.5% diagnosed with primary infertility, and 45.5% with secondary infertility. CAM usage was reported by 52.2% of participants, with herbal treatments being the most prevalent (e.g., fenugreek 26.9%, argell 20.2%). Spiritual healing (11.4%) and folkloric methods (9.5%) were also noted. Most users (76.5%) did not disclose CAM usage to healthcare providers, citing beliefs in safety (56.8%) and effectiveness (39.4%). Family (72%) and friends (46%) significantly influenced CAM use. Infertility duration and rural residence were associated with CAM usage (p=0.002). The study underscores a high prevalence of CAM usage among Sudanese infertile women, primarily herbal remedies, and emphasizes the importance of healthcare providers engaging patients in CAM utilization.